Columbiners: The activity of Serial Killer Fandom within True Crime Community - Kopeć, Martyna (Literatura Ludowa. Journal of Folklore and Popular Culture, 2021)
Eric Harris and Dylan Klebold are responsible for one of the most tragic mass school shootings in the US, know as The Columbine High School Massacre. This event brought about nation-wide moral panic concerning the depiction of violence in digital games, music and film. Interestingly, the teen murders have accumulated a fan base whose members are active online and refer to themselves as Columbiners. This fandom is a peculiar subgroup of True Crime Community, a larger community interested in criminology and the psychology of felons. The worship-like admiration of both serial and mass killers – particularly by women – is not a new phenomenon; there have been attempts to explain it away in the context of paraphilia and evolution. However, the fans of Columbine High School shooters elude such interpretations. This article analyses the case of Columbine fandom to demonstrate that the fascination with the murders need not involve sexualization, but can develop through empathizing and identifying with the criminals resulting from the radical recontextualization of their image in the digital pace.